If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(w + -5) = 3(1 + w) Reorder the terms: 4(-5 + w) = 3(1 + w) (-5 * 4 + w * 4) = 3(1 + w) (-20 + 4w) = 3(1 + w) -20 + 4w = (1 * 3 + w * 3) -20 + 4w = (3 + 3w) Solving -20 + 4w = 3 + 3w Solving for variable 'w'. Move all terms containing w to the left, all other terms to the right. Add '-3w' to each side of the equation. -20 + 4w + -3w = 3 + 3w + -3w Combine like terms: 4w + -3w = 1w -20 + 1w = 3 + 3w + -3w Combine like terms: 3w + -3w = 0 -20 + 1w = 3 + 0 -20 + 1w = 3 Add '20' to each side of the equation. -20 + 20 + 1w = 3 + 20 Combine like terms: -20 + 20 = 0 0 + 1w = 3 + 20 1w = 3 + 20 Combine like terms: 3 + 20 = 23 1w = 23 Divide each side by '1'. w = 23 Simplifying w = 23
| -5(p-1)=-p+29 | | -15z=-11 | | -15z=11 | | 4(w-1)=3(1+w) | | -x+7-6x=29-3x | | -3(-6-8v)=3v-3 | | 5(3x-1)-3(2x-3)=8x+4 | | (7y-4)+2y= | | -6+5u= | | -39+5n=6(2n-6)-3 | | 7x+7=8x+7 | | -39+5b=6(2n-6)-3 | | b^2-9b+14=0 | | 2(3z+5)-7=89 | | h(t)=-16t^2+32t+178 | | 10(8-x)=30 | | 4(x-3)=4x+12 | | 4n=3.6-2n | | X(32-12)=80 | | c-d+e=a | | 4(12-x)=36 | | 27x+17y =23x+y | | 2-5[3x-(4+2x)]= | | 2(x-6)=4(x+5) | | 3(g+1)+5=7 | | (12-x)+5=13 | | X^2+14-51=0 | | h=-16t^2+32t+178 | | 4m=26 | | 2a=0.35-5a | | (8-x)+23=28 | | 8-(d-2)=11 |